2017
DOI: 10.5350/sleep.hypn.2017.19.0146
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Eye Movement Desensitization and Reprocessing (EMDR) and Duloxetine Treatment Outcomes in Women Patients with Somatic Symptom Disorder

Abstract: Somatic symptom disorder (SSD) is a debilitating disorder that significantly diminishes quality of life and causes psychological distress such as anxiety and depression. The paper explored the efficiency of the eye movement desensitization and reprocessing (EMDR) therapy in SSD. The current investigation is a clinical trial investigating the effectiveness of eye movement desensitization (EMDR) therapy in the treatment of 31 first-diagnosed SSD patients in comparison to age, education and marital status matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…(Brown et al, 1997 ) (Demirci et al, 2017 ) (Royle, 2008 ) see Supplementary Table 4L. A multiple case study showed (Brown et al, 1997 ) (Demirci et al, 2017 ) (Royle, 2008 )…”
Section: Resultsmentioning
confidence: 97%
“…(Brown et al, 1997 ) (Demirci et al, 2017 ) (Royle, 2008 ) see Supplementary Table 4L. A multiple case study showed (Brown et al, 1997 ) (Demirci et al, 2017 ) (Royle, 2008 )…”
Section: Resultsmentioning
confidence: 97%
“…Relative to somatic disorders, one group study (Demirci et al, 2017 ) compared the administration of Duloxetine vs. six weekly sessions of 90 min EMDR in patients diagnosed with Somatic Symptoms Disorder (SSD). Results showed that both groups significantly improved on all measures, however, the improvement was higher in the EMDR group compared to Duloxetine, suggesting that EMDR may be considered as a first-line treatment in SSD.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, the effect of EMDR was described in patients with persistent physical complaints without a somatic substrate, namely body dysmorphic disorder (BDD), 100 somatic symptom disorder, 101 and chronic fatigue syndrome: 102 see Supplementary Table 4L. A multiple case study showed a positive effect of EMDR on BDD symptomatology in six out of seven included patients.…”
Section: Persistent Physical Complaintsmentioning
confidence: 99%
“…Both interventions showed a statistically significant reduction of somatization, anxiety and depression, with a superior effect of EMDR. 101 A case study found favorable effects of EMDR in a patient with chronic fatigue syndrome: there was a reduced need for sleep and energy levels were higher, which remained at follow-up. 102 Internal medicine…”
Section: Persistent Physical Complaintsmentioning
confidence: 99%